Analisis Perilaku Pengguna E-Kinerja Menggunakan Model UTAUT - Suparyati Suparyati (KILAT, 2019)
This study analyzes the behavior of E-Kinerja users at the Maros Veterinary Center using the UTAUT Model. E-Kinerja is a tool to assess the performance of employees with the status of the State Civil Apparatus (ASN) online in all work units of the Ministry of Agriculture of the Republic of Indonesia. The purpose of this study is to prove that the determinants of the use of E-performance (performance expentancy, effort expentancy, social influence, and facilitating conditions) influence the intention to behave on users (behavioral intention). The number of respondents in this study were 42 ASN in various ranks and classes. The results of the study show that the level of ASN's acceptance of E-Kinerja received a positive response. This can be seen from each average value of the variables in the range of 3.54 - 4.34 (on a scale of 1 to 5) on the questionnaire that has been distributed. In addition it was also found that Social Influence has a positive influence on Behavioral Intention in the use of E-Kinerja. Whereas Habit has a positive influence on Use Behavioral in the use of E-Kinerja in BBVet Maros. As for the Performance Expentancy, Effort Expentancy, and Facilitating Conditions variables on Behavioral Intention, as well as the Facilitating Conditions and Behavioral Intention variables on Use Behavioral, no positive effect was found.